Smart Interactive Learning Websites for Digital Literacy Empowerment: Integrating Artificial Intelligence, Gamification, and Learning Analytics - Aisyah Faradhilah Yasmin; Wasino Wasino; Muzakki Bashori (Proceedings of International Conference on Science, Education, and Technology, 2026)
The rapid advancement of digital technology has increased the demand for effective digital literacy education, yet existing learning platforms often lack adaptive and engaging mechanisms to support diverse learner needs. This study aims to design, develop, and evaluate an intelligent interactive learning website that integrates artificial intelligence (AI), gamification, and learning analytics to empower digital literacy competencies among learners. A design-based research (DBR) methodology was employed, involving an iterative cycle of analysis, design, development, implementation, and evaluation with a small group of elementary school students. The AI component facilitated personalized learning paths through adaptive content recommendations, while gamification elements including badges, leaderboards, and a points system increased learner motivation and engagement. A learning analytics dashboard provided real-time insights into learner progress and behavioral patterns for both students and instructors. Findings demonstrated a significant improvement in digital literacy scores (p < 0.01), with a 34% increase in learner engagement. This study provides a replicable framework for developing intelligent education platforms and demonstrates that the convergence of AI, gamification, and learning analytics is a transformative approach to fostering digital literacy in higher education contexts.